2023
DOI: 10.3390/en16052449
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Mineral Dissolution and Carbonation Efficiency Applied to pH-Swing Mineral Carbonation for Improved CO2 Sequestration

Abstract: Mineral carbonation incurs high operating costs, as large amounts of chemicals and energy must be used in the process. Its implementation on an industrial scale requires reducing expenditures on chemicals and energy consumption. Thus, this work aimed to investigate the significant factors involved in pH-swing mineral carbonation and their effects on CO2 capture efficiency. A central composite rotatable design (CCRD) was employed for optimizing the operational parameters of the acid dissolution of serpentinite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Furthermore, Arce et al [34] investigated temperatures ranging from 25 • C to 100 • C and discovered that all solutions employed at 100 • C obtained the highest Fe 2+ and Mg 2+ elution efficiency. A similar trend was reported by Galina et al [35], in that higher temperature (100 • C) leads to higher elution efficiency of Mg 2+ using 2.5 M HCl solution. Moreover, Rahmani [26] used red gypsum (mainly consisting of calcium sulfate and hematite) as feedstock material and achieved up to 63% Ca 2+ elution using 1.5 molar (M) sulfuric acid at 70 • C for 2 h. Kim and Jung [20] used cement kiln dust as feedstock and used citrate, malonate, and adipate salts to extract Ca 2+ , and reported that citrate had promising results and could extract up to 42% of Ca 2+ using 0.1 M concentration at 80 • C. Tier et al [36] assessed different acids, bases, and ammonium salt solutions to extract Fe 2+ and Mg 2+ using serpentine samples as feedstock, where 2 M HCl showed promising results that can extract up to 67% of Fe 2+ in 2 h at 70 • C. On the other hand, Razote et al [37] used iron-rich siltation pond waste as feedstock and reported extraction efficiency of Fe 2+ up to 94% using 2.5 M HCl at 75 • C in 2.5 h. Based on the previous studies, results with higher temperatures, concentrations, and higher reaction times for leaching or elution efficiency remain unpractical, e.g., due to energy consumption and its associated costs.…”
Section: Introductionsupporting
confidence: 88%
“…Furthermore, Arce et al [34] investigated temperatures ranging from 25 • C to 100 • C and discovered that all solutions employed at 100 • C obtained the highest Fe 2+ and Mg 2+ elution efficiency. A similar trend was reported by Galina et al [35], in that higher temperature (100 • C) leads to higher elution efficiency of Mg 2+ using 2.5 M HCl solution. Moreover, Rahmani [26] used red gypsum (mainly consisting of calcium sulfate and hematite) as feedstock material and achieved up to 63% Ca 2+ elution using 1.5 molar (M) sulfuric acid at 70 • C for 2 h. Kim and Jung [20] used cement kiln dust as feedstock and used citrate, malonate, and adipate salts to extract Ca 2+ , and reported that citrate had promising results and could extract up to 42% of Ca 2+ using 0.1 M concentration at 80 • C. Tier et al [36] assessed different acids, bases, and ammonium salt solutions to extract Fe 2+ and Mg 2+ using serpentine samples as feedstock, where 2 M HCl showed promising results that can extract up to 67% of Fe 2+ in 2 h at 70 • C. On the other hand, Razote et al [37] used iron-rich siltation pond waste as feedstock and reported extraction efficiency of Fe 2+ up to 94% using 2.5 M HCl at 75 • C in 2.5 h. Based on the previous studies, results with higher temperatures, concentrations, and higher reaction times for leaching or elution efficiency remain unpractical, e.g., due to energy consumption and its associated costs.…”
Section: Introductionsupporting
confidence: 88%
“…At 100 °C with 2.5 M HCl, 96% magnesium extraction was achieved in 120 min and 91% in 30 min. 22 Overall, the research improved the understanding of process parameters for serpentinite Mg extraction and highlighted the potential of serpentinite tailings for stable carbonate production, reducing waste disposal and aiding carbon sequestration through mining waste valorization. It encompassed the concurrent assessment of mechanical activation via particle size reduction and chemical activation through leaching agents.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Results indicated that the temperature significantly affects magnesium dissolution. At 100 °C with 2.5 M HCl, 96% magnesium extraction was achieved in 120 min and 91% in 30 min …”
Section: Introductionmentioning
confidence: 99%
“…An examination of these works revealed that 3 papers (10%) utilized experimental methodology, 6 papers (21%) discussed the reported results and compared them with their findings, and 20 papers (69%) cited 1 or more of Dr. Santos’s papers in the introduction section of their papers to explain a concept (Table S1 in the Supporting Information). More details and discussion about these relevant studies ,, are available in the Supporting Information file alongside other analyses on citation usage, publication sources, country, institutional collaboration analyses, and paper classification according to scientific disciplines and the United Nations Sustainable Development Goals. A scientometric analysis is a powerful tool for researchers to gauge the impact of their work and to connect with the broader scientific community beyond what other networking activities, such as conferences and webinars, allow.…”
Section: Scientometric Analysismentioning
confidence: 99%